Cultural Harmonization: Religious and Inter-Cultural Relations in Calengsai Arts - Abdallah Putra, Aqiel Sifa'; Lutfi, Mutohar; Fiani , Okta; Prakoso, Rico Anggit (Institut Seni Indonesia Denpasar, 2025)
The existence of Indonesian cultures and arts are rich in thought that is extraordinary to be explored, one of them is the typical Banyumas performance art, namely Calengsai (Calung, Lengger, and Barongsai), which is a local wisdom with a myriad of exploration sides for the people. This research tries to re-explore a Calengsai from the perspective of religious and intercultural relations, which mostly previous researchers only focus on the cultural and tourism aspects. This re-exploration of religious and intercultural studies is focus on model of cultural harmonization which purposed to break the conflict in the inter-cultural aspect that exist in Calengsai. The descriptive qualitative analysis is applied on this research to help the researchers to explore the evidence of the data which taken from the field collection. The study finds that Calengsai acts as a ‘third space’ of cultural hybridity where Javanese and Chinese traditions met through shared spiritual rituals, offering a scientific contribution to postcolonial and symbolic-interactionist scholarship by revealing how art creates new intercultural meanings.